The C19007T polymorphism of ERCC1 and its correlation with the risk of epithelial ovarian and endometrial cancer in korean women : A case control study - JO, Hoenil; KANG, Sokbom; SUNG IL KIM; JAE WEON KIM; NOH HYUN PARK; YONG SANG SONG; PARK, Sang-Yoon; SOON BEOM KANG; HYO PYO LEE (Gynecologic and obstetric investigation, 2007)
Excision repair cross-complementing group 1 (ERCC1) is a major DNA repair protein. Recent studies have addressed the association between ERCC1 polymorphism and carcinogenesis. We investigated a polymorphism of ERCC1 at nucleotide 19007 (C-->T, Asn118Asn) in 94 epithelial ovarian cancer patients, 102 endometrial cancer patients, and in 329 control subjects. We observed no evidence of associations between the C19007T ERCC1 polymorphism and risk of epithelial ovarian or endometrial cancer, which had the same adjusted odds ratios of 0.91 (p = 0.711, 0.691 respectively). Our findings suggest that the C19007T ERCC1 polymorphism is unlikely to play an important role in epithelial ovarian or endometrial cancer in Korean women.